Vascular inflammation in moderate‐to‐severe atopic dermatitis is associated with enhanced Th2 response. Issue 10 (4th May 2021) - Villani, Axel P.; Pavel, Ana B.; Wu, Jianni; Fernandes, Marie; Maari, Catherine; Saint‐Cyr Proulx, Etienne; Jack, Carolyn; Glickman, Jacob; Choi, Seulah; He, Helen; Ungar, Benjamin; Estrada, Yeriel; et al.
Abstract: Background: In atopic dermatitis (AD), some studies have shown an association with increased cardiovascular disease in certain populations. However, other investigations found modest or no association. Despite conflicting results, molecular profiling studies in both AD skin and blood have demonstrated upregulation of atherosclerosis and cardiovascular risk‐related markers. However, the underlying mechanisms connecting AD to vascular inflammation/atherosclerosis are unknown. In this study, we aim to determine factors associated with vascular inflammation/atherosclerosis in AD patients. Methods: We used 18‐FDG PET‐CT to characterize vascular inflammation in AD patients and healthy subjects. In parallel, we assessed their skin and blood immune profiles to determine AD‐related immune biomarkers associated with vascular inflammation. We also assessed levels of circulating microparticles, which are known to be associated with increased cardiovascular risk. Results: We found significant correlations between vascular inflammation and Th2‐related products in skin and blood of AD patients as well as atherosclerosis‐related markers that were modulated by dupilumab. Circulating levels of endothelial microparticles were significantly higher in severe AD patients and tended to correlate with vascular inflammation assessed by PET‐CT. Conclusion: Vascular inflammation in AD is associated with enhanced Th2 response and clinical severity, which may explain cardiovascular comorbidities observed in select AD populations. Larger prospective studies are needed to further evaluate vascular inflammation and cardiovascular events and mortality in AD patients. Finally, as dupilumab treatment demonstrated significant modulation of atherosclerosis‐related genes in AD patients compared to placebo, these data suggest that modulation of vascular inflammation with systemic treatment should be explored in patients with AD. Abstract : In 26 healthy controls and 30 atopic dermatitis patients, we evaluated their skin and blood immune profiles and characterized vascular inflammation using 18‐FDG PET‐CT and levels of circulating microparticles. Significant correlations between vascular inflammation and Th2 products in atopic dermatitis were identified. Circulating levels of endothelial microparticles were significantly higher in severe AD and showed correlation trends with vascular inflammation assessed by PET‐CT. Abbreviations: 18‐FDG‐PET‐CT 18‐fluorodeoxyglucose‐positron emission tomography‐computed tomography; C, control; CCL2, C‐C motif chemokine ligand 2; EMPS, endothelial‐derived microparticles; LS, lesional skin; NL, non‐lesional skin